Calendering of non-isothermal viscoelastic sheets of finite thickness: A theoretical study - Zahid Muhammad; Souayeh Basma; Ali Fateh; Farmer M.; Rahmat Fiza; Ilyas Muhammad (Applied Rheology)
In this article, the sheeting of pseudoplastic material under non-isothermal conditions has been studied. It is an excellent forecasting instrument for sheeting, where the thickness of the sheet is relatively thin in relation to the roll size, according to theoretical study based on the lubrication theory. At the calendering process, the detachment point is determined by taking the material parameter’s impact into account. The governing equations are derived for the constitutive equation of the Carreau fluid with momentum and energy equations. Suitable non-dimensional parameters are used to develop the non-linear partial differential expressions into ordinary differential systems. The maximum pressure, roll separating force, normal stress effect, and power delivered to the fluid by rolls are among the engineering-relevant quantities that are determined. Moreover, a graphic analysis is conducted to examine the impact of different material parameters on the temperature profile, pressure gradient, velocity profile, and pressure distribution. The results specific mechanism is explained in depth.